Rhodium-catalysed hydroacylation or reductive aldol reactions: a ligand dependent switch of reactivity. - Osborne, J; Willis, M (2008)
The pathway for the combination of enones and beta-S-substituted aldehydes using Rh-catalysis can be switched between a hydroacylation reaction or a reductive aldol reaction by simple choice of the phosphine ligand; this catalyst controlled switch allows access to new ketone hydroacylation products; useful 1,4-diketone intermediates for the synthesis of N-, S- and O-heterocycles.